PERLINDUNGAN HAM BAGI ANGGOTA POLRI YANG MELAKSANAKAN TUGAS PENGAMANAN UNJUK RASA BERDASARKAN UNDANG - UNDANG NOMOR 39 TAHUN 1999 TENTANG HAM - Bintang Pamungkas, Ghozali; Sudarto (LEX LAGUENS: Jurnal Kajian Hukum dan Keadilan, 2024)
Demonstrations are activities carried out by one or more people to express their thoughts verbally, in writing and so on demonstratively in public. It is not uncommon for demonstrations to result in riots against members of the National Police. Protection of Human Rights for members of the Indonesian National Police in securing demonstration duties is an important aspect that must be considered. This research will discuss the protection of human rights for members of the National Police who carry out security duties at demonstrations and the obstacles faced by members of the police in dealing with demonstrations. The legal research method used is a normative juridical legal research method supported by empirical data. Using a statutory approach and a conceptual approach. obtained from primary, secondary and tertiary legal material sources. Human Rights are a set of rights that are inherent in the nature and existence of humans as creatures of God Almighty and are His gifts that must be respected, upheld and protected by the state, law, government and everyone for the sake of honor and protection of human dignity. including members of the National Police. Protection of Human Rights for Police Members Carrying Out Demonstration Security Tasks includes the Right to Life, the Right to Obtain Justice in the Legal Process, the Right to obtain legal assistance and the Right to Obtain Protection from Violence. Obstacles faced by members of the National Police in dealing with demonstrations include lack of personnel, lack of equipment, anarchic attitude of the masses, provocations and bad weather.